SUSTAINABLE DEVELOPMENT GOALS (SDGS) DAN PENERAPAN PRINSIP SYARIAH: EVALUASI DAMPAK EKONOMI DAN SOSIAL - Styabudi, Wahyu (JSE: Jurnal Sharia Economica, 2025)
This research aims to explore the role of Islamic economics in supporting the achievement of the Sustainable Development Goals (SDGs) in Indonesia, with a focus on poverty alleviation, reducing social inequality, and inclusive economic development. Using the literature study method, this research analyzes various literatures related to Islamic economics, SDGs, and their implementation in Indonesia, with the aim of understanding the relationship between the two and identifying challenges and opportunities. The results show that the Islamic finance sector, which includes Islamic banks and Islamic microfinance institutions, has great potential in providing equitable access to finance and helping the poor, especially in the small and medium enterprise (SME) sector. The halal industry sector has also shown significant contribution to the national economy by creating jobs and increasing Indonesia's competitiveness in the global market. However, the main challenges faced are unclear regulations, low public understanding of Islamic economics, and limited infrastructure that hinders access to Islamic financial services, especially in remote areas. This study concludes that to optimize the potential of the Islamic economy in supporting the SDGs, it is necessary to strengthen regulations, improve Islamic economic education, as well as cooperation between the government, the private sector, and the community.